ANALISIS YURIDIS STRICT LIABILITY SEBAGAI PERTANGGUNG JAWABAN PIDANA KORPORASI TERHADAP DUMPING LIMBAH B3 KE MEDIA LINGKUNGAN BERDASARKAN UNDANG – UNDANG NOMOR 32 TAHUN 2009 TENTANG PENGELOLAAN DAN PERLINDUNGAN LINGKUNGAN HIDUP - Ganda Martunas Sihite; Zulfikar Jaya Kusuma; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The principle of strict liability is criminal liability which is charged tothe perpetrators of criminal acts with no errors. In its development, the regulationis always associated with environmental laws. In Indonesia, the principle of strictliability is contained in the provisions of Law Number 32 of 2009 concerningManagement and Environmental Protection in article 88. Implementation of lawenforcement against B3 waste dumping by corporations often causes injusticeagainst the community as victims. This departs from the understanding of lawenforcers who do not apply the principle of absolute liability (strict liability) aswell as an understanding of these principles which must be straightened outespecially with regard to articles and paragraphs a quo which are easilyinterpreted incorrectly.This research is a normative legal research that is research thatexamines secondary material or based on standardized rules that have beenrecorded whose scope of discussion is about legal principles, namely the principleof geen straft zonder schuld, and the principle of benefits; caution, justice listed inthe provisions of article 2 letters e, f, and g of UUPPLH-2009. So it is clearly andin detail illustrated the problem to be studied. Data sources used are secondarydata sources consisting of primary legal materials, secondary legal materials, andtertiary legal materials. Data collection techniques used by the literature reviewmethod.From the results and discussion that have been reviewed, the criminalliability for the B3 waste dumping crime against corporations based on theprinciple of strict liability, its application is very effective. Then the minimumapplication and understanding of the precautionary principle as stated in theUUPPLH-2009 principle in article 2 letter f becomes the reason for theimposition of criminal liability towards corporations based on the principle ofstrict liability. Furthermore, ideally the principle of strict liability for B3 wastedumping by corporations based on UUPPLH-2009 must consider that the elementof error as an embodiment of the principle of